Adolescent Responses to the Social Campaign Video on Kemdikbud.RI Account about Cyber-sexual Harassment - Rumahorbo, Karinda Amilia; Mutiaz, Intan (Indonesian Journal of Visual Culture, Design, and Cinema, 2023)
The primary purpose of a social campaign is to change a person's behavior or attitude regarding some social issues under the message conveyed by the communicator. It is described as persuasive communication. Furthermore, this study aimed to analyze the video content of the #GerakBersama social campaign from the cerdasberkarakter.kemdikbud.ri account about cyber sexual harassment and the audience's responses to the campaign related to awareness of this new phenomenon on social media. This study used mixed methods with data collection through in-depth interviews and surveys to obtain a thorough understanding from audiences and advertising experts regarding video advertising messages. The authors used Aristotle's theory of persuasion communication with three main pillars, namely ethos, pathos, logos, and the AISAS communication model to analyze the responses of the campaign video. These theories were processed and modified to obtain conclusions about the target audience's response to social advertisement videos regarding cyber-sexual harassment and to identify persuasive communication strategies in social campaigns as a reference for advertising professionals and academics in responding to new social problems in online media. The study results were also expected to reference further communication strategies and understanding related to persuasive communication in advertising and social campaigns.